Limits and possibilities experienced by nurses in the treatment of women with chronic venous ulcers - Silva, Marcelo Henrique da; Jesus, Maria Cristina Pinto de; Merighi, Miriam Aparecida Barbosa; Oliveira, Deíse Moura de (Revista da Escola de Enfermagem da USP, 2014)
Objective To understand the experiences and expectations of nurses in the treatment of women with chronic venous ulcers. Method Phenomenological research was based on Alfred Schütz, whose statements were obtained in January, 2012, through semi-structured interviews with seven nurses. Results The nurse reveals the difficulties presented by the woman in performing self-care, the perceived limitations in the treatment anchored in motivation, and the values and beliefs of women. It showed professional frustration because venous leg ulcer recurrence, lack of inputs, interdisciplinary work and training of nursing staff. There was an expected adherence to the treatment of women, and it emphasized the need for ongoing care, supported self-care and standard practices in treatment. Conclusion That treatment of chronic venous leg ulcers constitutes a challenge that requires collective investment, involving women, professionals, managers and health institutions.